Comparative Analysis of Quality of Life Questionnaires in Low Vision Patients: QOL in Low Vision Patients - Jabbar, Maryam; Asghar, Syeda Saima; Gillani, Syeda Sidra; Saeed, Maria; Akram, Zahra; Jabbar, Khadija (Pakistan Journal of Health Sciences, 2023)
Low vision affects large number of people globally, which can interfere with daily activities and lower quality of life. Objective: To evaluate the results of the Low Vision Quality of Life Questionnaire (LVQOL) and the National Eye Institute VFQ-25 as measures of patients’ quality of life. Methods: Between August-October 2022, a comparative cross-sectional study was carried out at Madina Teaching Hospital, Faisalabad. Through Non-Probability Purposive Sampling Technique, 40 patients were included. Participants who were between the ages of 25 and 55, having visual acuity of less than 6/18 and had a visual field that did not extend more than 10° from the fixation point were considered. Every patient underwent a thorough ocular examination, which included testing for near visual acuity, BCVA, tonometry, fundus examination, and slit lamp bio microscopy. Results: Participants’ average age was 47 ± 2.71. 17(42.5%) were female, whereas 23(57.5%) were male. Demographic data were recorded. Retinitis pigmentosa affected 12(30%) of patients, and age-related macular degeneration affected 9(22.5%) of the patients. Remaining diagnoses included glaucoma 8(20%), albinism 4(10 %), diabetic retinopathy 4(10%) and degenerative myopia 3(7.5 %). NEI VFQ-25 and LVQOL questionnaire’s mean overall scores were 41 ± 5.02 and 44 ± 4.89 respectively. Ratings can vary from 0-100, with 0 representing the worst and 100 denoting no visual impairment. Conclusions: NEI VFQ-25 composite scores and LVQOL had a strong correlation. Especially useful for analyzing the growth of low-vision rehabilitation since they can be used to gauge the quality of life for people with vision impairment.